1976
DOI: 10.1002/ajh.2830010104
|View full text |Cite
|
Sign up to set email alerts
|

Sickle β‐thalassemia: Identical twins differing in severity implicate nongenetic factors influencing course

Abstract: 25-yr old female identical twins of Italian-American origin concordant for sickle beta-thalassemia were studied to explain their clinical differences. One of them has been severely affected from childhood with one aplastic crisis, an earlier onset of vaso-occlusive crises, and recent cardiac decompensation; the other twin shows no cardiac decompensation. Similar are their degree of anemia, RBC indices, blood volumes, absence of splenic sequestration, depression of pO2, elevation of p50 and 2,3-DPG, hemoglobin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…As siblings with sickle cell disease are likely to share the same ␤-globin genes and their linked regulatory seg-ments, we hypothesized that if some component of the regulation of HbF response to HU is linked to the ␤-globin gene cluster, then siblings might have concordant responses to treatment. Our data and very limited observations in untreated twins with sickle cell disease who have similar HbF levels whatever their disease phenotype support our hypothesis [25,26].…”
Section: Discussionsupporting
confidence: 85%
“…As siblings with sickle cell disease are likely to share the same ␤-globin genes and their linked regulatory seg-ments, we hypothesized that if some component of the regulation of HbF response to HU is linked to the ␤-globin gene cluster, then siblings might have concordant responses to treatment. Our data and very limited observations in untreated twins with sickle cell disease who have similar HbF levels whatever their disease phenotype support our hypothesis [25,26].…”
Section: Discussionsupporting
confidence: 85%
“…Two case reports (Joishy et al , 1976; Amin et al , 1991) and a pilot twin study (Weatherall et al , 2005) showed that despite identical β‐ and α‐globin genotypes and similarities in growth, haematological and biochemical parameters, the identical twins had quite different prevalence and severity of painful crises and some of the sickle complications. Although sample size of the twin study was small, it does suggest that environmental factors may be of greater importance in determining clinical expression and complications of sickle disease.…”
Section: Genetic Modifiers Of Sickle Cell Diseasementioning
confidence: 99%
“…A better understanding of the relationship between patients and their environment may allow significant improvements in health, by giving simple advice and facilitating the development of appropriate public health policies; genetic factors are generally less amenable to modification. [18][19][20] Similarly, people with SCD have a much more severe course in most of Africa compared to genetically similar patients in the northern hemisphere, and this is likely to be related to environmental factors, including infections, climate and access to healthcare. Equally, there are marked differences in clinical severity between patients with the Arab-Indian β S haplotype in India and the Middle East, with there being both mildly and severely affected patients; 21,22 these differences are likely to be at least partly attributable to environmental factors.…”
Section: Introductionmentioning
confidence: 99%